The Rise of the Female Voice in Roald Dahl's Matilda and Esio Trot - BASARİİA, ADA (İstanbul Kültür Üniversitesi, 2025)
This thesis analyzes the rise of the female voice in children's literature in relation to the construction of femininity within the sociopolitical and sociocultural context of 1980s-1990s Britain – a period marked by economic instability, neoliberal policies, and gender conservatism. Focusing on how patriarchal structures shape the conceptions of femininity, motherhood, intellectual autonomy, and "natural caregiving", this thesis analyzes these constructs within a feminist theoretical framework to demonstrate that female identity is not fixed but multiple, fluid, and elusive in its resistance to the patriarchal structure. In this context, Roald Dahl's Matilda and Esio Trot embody these arguments in narrative forms that reflect contrasting demonstrations of female agency. Viewed through a feminist lens, Dahl's Matilda presents a portrayal of female agency through the protagonist named Matilda – a child in the pre-operational stage of cognitive development who acquires her "telekinetic" powers as a consequence of her inner rage in response to patriarchal oppression in both domestic and public spheres. Her "telekinetic" powers, creative and analytical mind consequently become a weapon that helps Matilda resist the oppression of patriarchal authority. Matilda gains agency through emotional resilience and empathy that she acquires through autodidactic learning, which gradually shapes her identity and compensates for the neglect of her parents, Harry and Zinnia Wormwood. In addition to autodidacticism, the growing solidarity between Matilda and her teacher, Miss Honey, functions as a tool of subversion of patriarchal norms and gender expectations, such as passivity and conformity conveyed through her parents and the headmistress of Crunchem Hall, Miss Trunchbull. Analyzed through a feminist perspective, this novel highlights the vital importance of female solidarity and the presence of female agency, which are fundamental for the empowerment of the female voice across future generations. Dahl's Esio Trot is the second key source for this thesis, offering a different image of female agency through the character of Mrs Silver, a middle-aged widow. Although the novella is written in the third-person narrative, it mostly focuses on the thoughts and ambitions of Mr Hoppy, Mrs Silver's neighbor. Mr Hoppy is portrayed by Dahl as a shy retired man who longs for Mrs Silver's affection. However, from the feminist standpoint, Mr Hoppy is perceived as the representative of the patriarchal structure who aspires to fit in the constructed concept of masculinity, which is traditionally defined by physical power, dominance, and control. Once he is asked for assistance, Mr Hoppy uses the alternative, symbolic form of dominance characterized by strategic thinking and subtle manipulation. It is this third-person narrative that makes it plausible to analyze Mrs Silver's performance of "natural caregiving" prescribed to females by the patriarchal system through a feminist lens in relation to ethical vulnerability and the embodied language of care which therefore gives the presence of agency to Mrs Silver and functions as a form of subtle resistance to the patriarchal oppression. This thesis aims to analyze particular ways in which the children's literature fosters distinct types of female subjectivity, tailored to the cultural setting of their time as well as to compare two different images of female agency (open resistance to patriarchal structures in Matilda and strategic forms of adaptation and resistance in Esio Trot) within the feminist theoretical framework.
Keywords: Motherhood; “Natural Caregiving”; Female Agency; Patriarchal Structure; Subtle Resistance; Roald Dahl; Empathy; Autodidacticism; Feminism; Masculinity; Femininity; Children’s Literature; Matilda; Esio Trot